Bug Tracking Systems as Public Spheres. - Reagle Jr., Joseph (Techné: Research in Philosophy & Technology)
Based upon literature that argues technology, and even simple classification systems, embody cultural values, I ask if software bug tracking systems are similarly value laden. I make use of discourse within and around Web browser software development to identify specific discursive values, adopted from Ferree et al.'s "normative criteria for the public sphere," and conclude by arguing that such systems mediate community concerns and are subject to contested interpretations by their users.